To solve this, we first need to substitute the value of b from the first equation into the second equation:
a - 4 = 8
Now, we can solve for a by adding 4 to both sides:
a = 12
Now that we have found the value of a, we can substitute it back into the first equation to find the value of b:
12 - b = 4
Subtracting 12 from both sides gives us:
b = 8
So, the solution is a = 12 and b = 8.
To check this solution, we can substitute the values back into the original equations:
a = 12, b = 8
12 - 8 = 4 (true)12 - 8 = 4,8 (true)
Therefore, the solution is correct.
To solve this, we first need to substitute the value of b from the first equation into the second equation:
a - 4 = 8
Now, we can solve for a by adding 4 to both sides:
a = 12
Now that we have found the value of a, we can substitute it back into the first equation to find the value of b:
12 - b = 4
Subtracting 12 from both sides gives us:
b = 8
So, the solution is a = 12 and b = 8.
To check this solution, we can substitute the values back into the original equations:
a = 12, b = 8
12 - 8 = 4 (true)
12 - 8 = 4,8 (true)
Therefore, the solution is correct.